ANALISIS SISTEM PEMBERIAN KREDIT PADA KOPERASI PEGAWAI LOGISTIK PERUM BULOG KANWIL KALBAR - Jaurino; Septianus, Julio Caesar; Yahya, Rizky F. (Jurnal Akuntansi, Auditing dan Investasi, 2022)
This study aims to determine the credit system and negligent credit in the logistics employeecooperative of the bulog regional office of west borneo. This research includes qualitative research,the data used are in the form of outstanding loan data, the documents used, and the organizationstructure of the logistical employee cooperative organization of perum bulog west borneo regionaloffice. Data collection is by using , observation, interview, and literature study. which is thenanalyzed by analytical tools using Flowchart (Flow), ICQ ( Internal Control Quisioner), interview.The result of this study indicate that the organizational structure of the logistics employeescooperative of perum bulog alredy exists, but its implementation has not been carried out optimallywhere there is dual work by the savings and loan unis so that the work carried out is less focusedand concurrent work is also carried out by the treasurer where as credit disbursement andaccounting department and that is insparable from the lack of human resources. Meanwhile, thefactors that cause negligent credit are used by internal factors which are still not careful in analyzing credit, negligence in repaying loans, lack of credit supervision, as well as the lackof human resources. Exsternal factors, namely the existence of bad faith or elements of intentionallate payments made by members, dishonesty during interviews and the existence of urgent needsby members so that loan payments delayed.